Effect of glycoprotein IIb-IIIa receptor antagonism on platelet membrane glycoproteins after coronary stent placement - Gawaz, M; Ruf, A; Neumann, F J; Pogátsa-Murray, G; Dickfeld, T; Zohlnhöfer, D; Schömig, A (Thrombosis and haemostasis, 1998)
Platelet membrane glycoproteins play a crucial role in ischemic complications after coronary stenting. Glycoprotein IIb-IIIa blockade reduces adverse clinical events after angioplasty but is associated with rare but profound thrombocytopenia that might increase hemorrhagic complications. Changes in platelet membrane glycoproteins of patients with angina who underwent coronary stenting and were treated with the GPIIb-IIIa antagonist abciximab (n=20) or with heparin (n=23) were studied. GPIb-IIIa receptor blockade and membrane glycoproteins were evaluated with immunological markers in venous blood samples taken before. 10, 24, 48, 72, and 96 h after initial treatment with either abciximab or heparin. Patients receiving abciximab therapy showed a rapid inhibition of binding of fluorochrome-conjugated mAb CD41 and c7E3 concomitant with a reduction in platelet aggregation which was restored in part in the days after termination of abciximab infusion. Induction of ligand-induced binding sites on GPIIb-IIIa was increased in patients receiving abciximab. The expression of ligand-induced binding sites correlated inversely with platelet count. No significant change in platelet membrane markers were found in the heparin group. In vitro studies showed that abciximab induces ligand-induced binding sites on isolated platelets and on nuclear cells bearing recombinant GPIIb-IIIa. Abciximab rapidly achieves GPIIb-IIIa receptor blockade after coronary stent placement that might be beneficial in high-risk settings to bridge the delayed action of ticlopidine. Significant alterations of platelet membrane glycoproteins during GPIIb-IIIa antagonism might contribute to development of acute profound thrombocytopenia.